Conceptual model to contribute to the development and growth of technology-based spin-off at the National Autonomous University of Honduras (Journal of Management & Business, 2022)
Currently, universities are playing a very important role in the economic and social development of countries, strengthening the entrepreneurial spirit and being the source of many emerging companies. The objective of this study is to develop a conceptual model that allows identifying lines of entrepreneurship and base of entrepreneurs to promote the creation and / or development of spin off within the National Autonomous University of Honduras (UNAH), the research was developed based on the results of the scientometric analysis of the scientific basis for technological entrepreneurship in Honduras, scientific articles related to incubators/accelerators, Lean Startup methodology, spin off development, UNAH website, among others. The results allowed the generation of a conceptual model that relates the incubator/accelerators, scientific base of articles, analysis tool, Lean Startup methodology, lines of entrepreneurship, base of entrepreneurs, finally concluding that the UNAH has the necessary components for its consideration and testing.
Keywords: spinoff; incubators; entrepreneurs; lean startup methodology